(untitled) (Prostor, 2024)
This paper aims to synthesize recent knowledge about the churches built between 1492 and 1918 in the Kaštela area and present its characteristics obtained by research in the doctoral thesis of the first author. The research covered 18 churches located in the coastal area. Fourteen churches have been preserved, two were pulled down, while the existence of two other churches was detected on old maps and in written documents. After a genealogical and catalogue study, a typological and stylistic analysis of the churches has been made. The longitudinal aisleless churches as a dominant shape vary in dimensions, type of construction, construction solutions and elements of architectural decoration.